Die kleineren Dichtungen Heinrichs von Mügeln Zweite Abteilung - Stackmann, Karl (Deutsche Texte des Mittelalters, 2003)
This volume concludes the edition of Heinrich von Mügeln's smaller poems. This is the first complete edition of the hymns of one of the most important poets of the 14th century. The volume also contains two of Mügeln's Latin texts: 'Artes liberales' and 'Libri tocius biblie', two summaries on the liberal arts and the books of the Old Testament. The centerpiece of the volume is 'Der meide kranz', an allegorical poem about the struggle between the liberal arts and between the virtues and nature, written in honor of Emperor Charles IV. An index of names and words makes the entire edition accessible and thus forms an essential key to the author's oeuvre.